Teaching physicians-in-training to address racial disparities in health: a hospital-community partnership. - Jacobs, Elizabeth A. (Association of Schools of Public Health, 2003)
Racial and ethnic disparities in health care continue to be a major impediment to improving the health of many communities in the United States. Efforts must be directed at the multiple social, economic, and historic determinants of health disparities. In addition, health care providers must be aware of these determinants and must have the tools to address them in their individual relationships with patients. This article describes a partnership that arose out of the mutual recognition by a community organization and public hospital of the need to (a) teach physicians how to recognize the root causes of health disparities, (b) improve their cross-cultural understanding and communication, and (c) enhance their awareness of the capacity of community resources to positively impact their patients' lives.